Biomechanical evaluation of different fixation plates in medial opening upper tibial osteotomy - Esenkaya, Irfan; Misirlioglu, Mesut; Kelestemur, M. Halidun; Elmali, Nurzat; Fadillioglu, Ersin (Elsevier Science Bv, 2007)
In this biomechanical study, 25 in vitro calf tibial models were used in order to compare the stability of the plates under axial compression loading. A 10-mm medial opening gap was stabilized in each of the five calf tibial models either with four or two-holed rectangular shaped plates with wedges, with four-holed reversed L-shaped plates with wedges, with the combination of these two types of plates, or with six-holed anatomical T-plates. The compression behavior of the model was tested by using a universal mechanical testing system. The specimens fixed with the combination of plates with the four-holed reversed L-shaped and with two-holed rectangular shaped; or with six-holed anatomical T-plates, showed significantly better stability than those of others. Four different kinds of failure (slippage of wedge, lateral cortex fracture, damage and/or loosening of screws, and bending of plates) were observed on the models. When the average value of force loading on the plates that were designed by the first author was considered, the plates were stable and the average force values at these points were higher than the loading force on a knee during the normal paced walking or running conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: knee; unicompartmental osteoarthritis; proximal tibial osteotomy; high tibial osteotomy; biomechanics; plate designs